2011
DOI: 10.1007/978-3-642-23490-3_22
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Routing Protocols and Simulations in Delay-Tolerant Networks

Abstract: Abstract. Delay-Tolerant Networks (DTNs) are a type of emerging networks characterized by very long delay paths and frequent network partitions. For the distinct characteristics of DTNs, routing becomes one of the most challenging open problems. Recent years numerous approaches have been presented for addressing routing issues in DTNs. This paper surveys main DTN routing strategies and gives a comparison of them with respect to the performance metrics. Specially, we summarize the cardinal mobility models and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Message replication helps to increase the probability of message delivery because more nodes are responsible for delivering the message to the base station. The flooding routing protocols include Epidemic Routing, Two-Hop Relaying, Tree-Based Flooding and Prioritized Epidemic Routing [10][11][12].…”
Section: Delay Tolerant Networking (Dtn) Routing Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…Message replication helps to increase the probability of message delivery because more nodes are responsible for delivering the message to the base station. The flooding routing protocols include Epidemic Routing, Two-Hop Relaying, Tree-Based Flooding and Prioritized Epidemic Routing [10][11][12].…”
Section: Delay Tolerant Networking (Dtn) Routing Protocolsmentioning
confidence: 99%
“…In this strategy, knowledge about the network is required by the routing protocol and the nodes collect information about other nodes in the network to select the best path to forward the message to the destination [9]. Location-Based Routing, Source Routing, Per-Hop Routing and Per-Contact Routing belong to the forwarding family [10,12].…”
Section: Delay Tolerant Networking (Dtn) Routing Protocolsmentioning
confidence: 99%
“…However, its effectiveness relied on the number of devices and the maximum allowed delay [4]. In general, DTN routing protocols are classified in two categories: flooding-based protocol and forwarding-based protocol [14]. In flooding-based protocols, each node sends its messages to the nodes that it comes into contact.…”
Section: Existing Workmentioning
confidence: 99%
“…The routing strategy that we consider in this work is prediction-based routing [2]. We generalize predictionbased routing protocols as follows: Consider a node a that has a message for a destination node d. When the node a encounters another node b, it forwards a copy of the message to the node b if the probability of b encountering d (given as P bd ) is higher than the probability of a encountering d (given as P ad ).…”
Section: System Modelmentioning
confidence: 99%
“…In such scenarios, the mobility pattern of nodes plays an important role in the routing process. Prediction-based routing protocols [2] for Mobile DTNs take advantage of the mobility patterns of nodes to deliver messages. It has been shown that these protocols perform better than other protocols when nodes exhibit well known mobility patterns [3].…”
Section: Introduction Mobile Delay Tolerant Network (Mobile Dtns Ormentioning
confidence: 99%